Comparing the environmental performances of new and renovated school buildings - Oscar Mancinelli; Alessandro Pasquale Fantilli; Bernardino Chiaia (Acta Polytechnica CTU Proceedings, 2022)
Evaluating which is the best choice between renovating an existing construction or building a new structure in countries like Italy, where a huge post-war un-listed building heritage does not satisfy the current standards and the economic resources are limited, is not trivial. Several parameters come into play, such as such the extent of the construction work, the environmental cost of disposing old materials, the carbon footprint and volume of new materials. This paper is devoted to the analysis of two projects. The first consists of a renovation of a multi-storey existing school built in 1960s having total area of about 9900 m2. The second is a new construction of a three-story school having a total area of about 14000 m2 and made with timber. The results show that the existing school building, although having a lower embodied carbon related to materials, has a higher overall carbon footprint due to the CO2 emissions related to operational energy.